"Women, Men, Boys, and Girls": Analyzing the Implementation of Women, Peace, and Security in the United States. Issue 4 (13th October 2022) - Henshaw, Alexis
Abstract: More than 20 years after the passage of UN Security Council Resolution 1325 (2000), the United States is still in the process of institutionalizing its strategy on Women, Peace, and Security (WPS). While the Women, Peace, and Security Act (2017) established a legal mandate by which federal agencies are obligated to demonstrate efforts to mainstream gender in foreign policy, timely implementation has been hindered by confusion and disagreement over the aims of WPS. Drawing on elite interviews with 35 stakeholders working on WPS implementation across relevant institutions, I argue that implementation efforts in the United States have resulted in understandings of WPS that parse the agenda as an extension of familiar issues like the War on Terror, debates over reproductive rights, and issues of sexual harassment and equal opportunity. I demonstrate how feminist security studies and cognitive approaches to foreign policy analysis explain these outcomes.